Entrepreneurial and Sustainable Business Strategies in Bereavement Industry : Kuala Lumpur, Malaysia (Business Practices and Consumers Views) - Grgas, Jasminka (2014)
This study aims to investigate dimensions of Strategic Entrepreneurship (SE) business practices in bereavement industry (BI) in Kuala Lumpur and how these practices, with focus on sustainability issues, relate to consumers views. The study will evaluate business practices in BI based on Ireland’s (2003) model of SE with particular focus on sustainable entrepreneurial practices as they relate to constraint of availability of interment space in funeral homes in Kuala Lumpur. Information from regulatory bodies will be obtained through interviews as it relates to the issue of sustainable practices in BI, and constraint of interment space availability in urban areas. Consumer views will be evaluated through questionnaire and compared to current business practices and regulatory guidelines. Ireland (2003) identified four key dimensions of SE construct: Entrepreneurial Mindset, Entrepreneurial Culture and Entrepreneurial Leadership, Managing Resources Strategically, Applying Creativity and developing innovation and they lead to creation of competitive advantage with end result of wealth creation. Obtained findings suggest that bereavement industry in Kuala Lumpur is guided by National and international principles as it relates to sustainability and urban land development, however there was no obtained evidence about synchronized efforts between policy makers and industry on determining future strategic direction of industry. Perspectives from industry sample, regulators and consumers suggest that industry has room for improvement in developing systematic data collection/records, best business practices and professional association creation.